Ethylene and Auxin: Hormonal Regulation of Volatile Compound Production During Tomato (Solanum lycopersicum L.) Fruit Ripening - Tobaruela, Eric de Castro; Gomes, Bruna Lima; Bonato, Vanessa Caroline de Barros; Lima, Elis Silva de; Freschi, Luciano; Purgatto, Eduardo (Frontiers in Plant Science, 2021)
As the auxin-ethylene interaction in climacteric fruit ripening has been highlighted, the hormonal regulation of aroma changes in climacteric fruits requires clarification. The influence of both phytohormones on the volatile organic compound (VOC) metabolism was evaluated during tomato (Solanum lycopersicum L.) fruit ripening. Tomato fruits cv. Micro-Tom and Sweet Grape at the mature green stage were randomly grouped according to treatment with ethylene (ETHY), auxin (IAA), or both (ETHY+IAA). At middle ripening, Micro-Tom ETHY+IAA fruits present VOC profiles similar to those of ETHY fruits, while Sweet Grape presents VOC profiles closer to those of IAA fruits. At full ripeness, Micro-Tom and Sweet Grape ETHY+IAA fruits show profiles closer to those of IAA fruits, suggesting that the auxin overlaps the ethylene effects. The transcription of genes related to important tomato VOC biosynthesis evidences their regulation by both plant hormones. Additionally, the results indicate that the observed effects on the VOC metabolism are not restricted to the Micro-Tom cultivar, as these are also observed in the Sweet Grape cultivar. In conclusion, ethylene and auxin directly regulate the metabolic pathways related to VOC formation, impacting tomato aroma formation during ripening since Micro-Tom fruits apparently at the same maturation stage have different aromas.